Strategies for Improving The Quality of Islamic Education at MTS Muhammadiyah Kudus - Nur Hani'ah; Mohammad Zakki Azani (Journal of Educational Sciences, 2026)
The purpose of this study is to describe strategies and methods aimed at improving the quality of Islamic Religious Education learning at MTs Muhammadiyah Kudus. This study applies a qualitative approach through the use of observation, documentation, and interviews with three Islamic Religious Education teachers. The findings of the research show that the approaches applied to improve the quality of the learning process include objectives that focus on character development, the creation of contextual materials such as memorization of verses from the Qur'an and Hadith, worship practices, and interactive methods such as Index Card Match (ICM) and playing videos on Islamic history. Teachers act as role models and mentors, while students actively participate in learning and worship activities. Religious character building is carried out through the habit of performing congregational prayers, reading the Qur'an, reciting Asmaul Husna, and fasting on Mondays and Thursdays. The obstacles faced include limited facilities, diversity of teaching methods, and decreased motivation to learn. Overall, the strategies implemented by PAI teachers reflect the madrasah's vision of shaping students who are knowledgeable in science, noble in character, and excellent in achievement.